COMPREHENSIVE DIAGNOSIS AND PROGNOSIS OF PERIMENOPAUSAL OSTEOPOROSIS - Djalolova , Sh.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: The menopausal period is a physiological transition period in a woman’s life, which occupies the period of time between the reproductive phase and old age.During this period, against the background of age-related changes in the entire body, nevertheless, the involution processes dominate the reproductive system and are characterized by a gradual decrease and shutdown of ovarian function.In the menopausal period, changes such as vasomotor, emotional-vegetative or metabolic disorders occur. Material and methods: We assessed the condition of the skeletal system of 68 perimenopausal women aged 55 to 65 years. The condition of the women was assessed according to the following criteria: complaints, general examination, anamnesis, and also hormonal status, blood levels of Ca and vit. D, were assessed. Transdermal gel Estrogel was used as a hormonal drug. Results: Thus, the obtained data show that with age and changes in women’s lifestyle, there is a decrease in the concentration of estradiol in the blood, as well as a decrease in the amount of calcium and vitamin D in the blood. At the same time, X-ray examination in the initial period of osteoporosis reveals only one cystic change, and with age, multiple cystic changes in the bones are revealed. Densitometric examination allows for accurate diagnosis of the progression of osteopenia to osteoporosis. Conclusion: During the transition of a woman from perimenopause to postmenopause, clinical and laboratory signs of structural disorders of long tubular bones increase, which is associated with a decrease in hormonal function and the transition of osteopenia to osteoporosis. The most reliable diagnostic tests for detecting osteoporosis are densitometry, MRI and X-ray studies. The use of transdermal gel Estrogel relatively quickly improves the general condition of women in perimenopause, and it is very easy to use